Environmental health in Central and Eastern Europe - Donnelly, K. C. (Springer, 2006)
Complex chemical mixtures impact our health every day. In the United States, and also in Central and Eastern Europe, there are a number of locations where complex chemical mixtures have been released to environmental media. Although exposure to mixtures is common, minimal information exists to quantify these exposures, or to determine their impact on human or ecological receptors. These proceedings present some of the most current research conducted to quantify complex mixtures in the environment and investigate their potential impact on human health. Many of the manuscripts reported in these proceedings represent the most up-to-date measurements of population exposures in Central and Eastern Europe. These studies are of value to health and environmental professionals around the world as they develop strategies for assessing exposures, remediating contaminated environments, and improving public health. Mortality in northwestern bohemia in periods of high and low air pollution -- Air pollution in teplice and prachatice in 1995 and 2003: a comparison after 8 years -- Genotoxic activity of ambient air pollution in three european cities: Prague, Košice and Sofia: an 'In Vitro' study -- Human exposure to polyhalogenated hydrocarbons and incidence of selected malignancies -- Non-melanoma skin cancer incidence in relation to arsenic exposure: 20 years of observation -- Ecocytogenetics as a biomonitoring model for occupational exposure -- Cytogenetic damage detected in lymphocytes of donors from MałOpolska Region in Poland and cancer incidence in the follow-up studies -- An improved method for the biological monitoring of volatile compounds -- Changes in caddis larvae community composition: effect of unknown contaminants -- The effect of acrylonitrile on the frequency of chromosomal aberrations -- Biomarkers of air pollution exposure: follow-up study in policemen in prague -- Asbestos exposure and its health effects -- Environmental conditions and health outcomes for children in Armenia: environment and child health in Armenia -- The carcinogenic risk of occupational exposure to quartz dust: biomonitoring results -- Polychlorinated biphenyl-mediated inflammatory signaling: implications in atherosclerosis -- Blood lead levels and hand lead contamination in children ages 4-6 In Copsa Mica, Romania -- Assessment of fescue cultivars for phytostabilization effectiveness -- Health risk assessment in children of the Isykkol Region of the Kyrgyz Republic -- Arsenic health risk assessment and molecular epidemiology project in Slovakia -- A public health approach to identifying and reducing lead exposures at a mining site -- Combined effect of selected industrial fibrous dusts and tobacco smoke on the respiratory tract: combined effect of mineral fibers and tobacco smoke... Dusts containing quartz and carcinogenicity risk in mines: epidemiological study -- Energy management of waste clean-up sites, avoiding secondary air impacts to human health -- Field study and modeled transport of chlortoluron in different soil types of the Czech Republic -- Methods for determination of soil hydraulic properties -- Urban soils: a part of man's environment -- Children, health and their environment -- New knowledge about the impact of environmental exposure to PAHs -- Monitoring of organohalogens body burden of the Czech population.